PENGARUH UPAH KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA HOME INDUSTRI JENANG "MILAH" DI KABUPATEN PONOROGO - Safrida Riana Candra (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
The purpose  of this study  was to determine  the prevailing  wage  in the home industry porridge  “MILAH”,    to determine  the productivity  of the employees  home industry porridge “MILAH”,    as well  as to determine  whether  or not the effect  of wages  on employee  productivity  at home industry  porridge "MILAH"  in Ponorogo.  The samples  in this  study  using  a sample  that  is saturated  all the  employees   home  industry  porridge “MILAH”, amounting  to 22 people.  Data collection  using documentation   and interview. In analyzing  the data used  for regression   testing  method  examines  the  hypothesis  proposed  in  this  study. The  results  showed  that  wages  have  relationships   and  a positive influence on employee  productivity  at home industry porridge  “MILAH”   in Ponorogo.  It is obtained  from the correlation  test showed  the value rhitung 0.867 whereas  rtable 0.423, on the other  hand  Sig(hit) is 0.000  while  the magnitude   Sig(prob) 0.05. This  means  that the value of rhitung >= rtable (0.867 >= 0.423) or Sig(hit) <= Sig(prob) (0.000 <= 0.05) meaning  a rejection  of H0 which shows  that wages  have a relationship  with  employee  productivity   at borne  industry  porridge  “MILAH”   in Ponorogo.  Further  test results  were also obtained  Fisher, Fhitung value is 60.542 while the value Ftable 4,351, on the other hand is Sig(hit) 0.000 while the magnitude   Sig(prob) 0.05. This  means  that the value  of Fhitung >= Ftable (60.542>= 4.351) or Sig(hit) Sig(prob) (0.000 d" 0.05) meaning  a rejection  of H0 which  indicates  that there are significant wage on employee productivity  at home industry porridge “MILAH”  in Ponorogo. Also  obtained  results  of the t test, thitung is 7,781 while ttable of 2,086, on the other hand Sig(hit) value  is 0.000  while  Sig(prob)  0.05.  this   means  that the value  of thitung > ttable (7.781 > 2.086)  or  Sighit< Sigprob  (0.000  < 0.05)  meaning  a rejection  of H, which  shows  that there are different  effects on the productivity   of the employee  wages at home industry  porridge "MILAH"   in Ponorogo.  Results  R2 of 0.752  indicates  that 75.20/0 of the variable  productivityof employeesaffectedbywagelabor,whiletheremaining24.8%isinfluencedby